Perancangan Internet Of Things Smart Farm Untuk Pengaturan Suhu Pada Day Old Chicken (DOC) Berbasis Arduino - Panji Nur Fauzan; Muhammad Yasser Arafat (CV. Multi Kreasi Media, 2023)
The temperature and humidity control system is very helpful for farmers to maintain the stability of the temperature of the broiler chicken coop in order to achieve success for the breeders. In addition, the system can help both in terms of time efficiency and human labor because the system works automatically. The microcontroller will give instructions to turn off or turn on the humidity sensor where the sensor will read the room temperature of the broiler chicken coop then instruct Arduino to turn on the switch and turn on the lights. The fan that will be installed automatically in the chicken coop has an increase in air humidity. The method proposed to develop a temperature and humidity monitoring system is the observation method. Data collection was carried out directly on the object of the problem at Mr. Halimi's chicken farm. The author made direct observations when the farm manager was monitoring the chicks. Design of automatic control and monitoring of chicken coop temperature by utilizing Internet Of Things (IoT) technology using the Blynk application which is integrated with the NodeMCU ESP8266 module which is equipped with a DHT11 temperature sensor which functions as a temperature detector in the cage. In addition, this tool is equipped with a 16x2 LDC to display the results of temperature detection, as well as a relay that functions to control the fan and turn on the lights in the chicken coop.